CHARACTER EDUCATION VALUES IN SPARE PARTS MOVIES - Rusdy Ananda Ananda; Fajariski Wahyudi Siregar (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2020)
This research aims to analyse the values of education contained in the movie "Spare Parts" which can be used as a source in the aspect of education in everyday life. This type of research is the study of libraries, using a qualitative descriptive approach. The primary data source on this study was to observe directly the movie "Spare Parts". Data collection techniques by watching, recording and studying literature. The results showed that there were character education values contained in the film Spare Parts. The values of character education in the movie Spare Parts can be understood from the dialogue and scenes played by the players. Spare Parts Movie has many meanings about the character education in it, which the author of the Raangkum include the values of discipline, hard work, creative, curiosity, appreciating achievement, friendly/communicative. The meaning of the FIM will be very relevant in education, especially in Indonesia, that is a character education. This Film can be used as a learning medium aimed at character building.